Determinants of Environmental Sanitation Related to the Incidence of Diarrhea among Infants - Jernita Sinaga; Risnawati Tanjung; Eka Lestari Mahyuni; Helfi Nolia; Raflizar Raflizar (Universitas Ahmad Dahlan, 2021)
Background: Incidence of diarrhea increased by poor environmental conditions factors. The several factors of environmental health are housing, disposal waste, clean water supply, and sewerage. This study's purpose was to determine the determinants of environmental sanitation related to the incidence of diarrhea in infants at the work area of Pusat Kesehatan Masyarakat (Puskesmas) Singa, Karo District. Method: This research was quantitative research as a case study of diarrhea among infants in Puskesmas Singa. The subjects were housewives who had infants and suffered from diarrhea in the last six months of the study, with 225 total population and 63 people selected by simple random sampling. The data analyzed used logistic regression to found the influence of environmental sanitation on diarrhea. Results: The results found there were six variables analyzed, there were three variables that influenced the incidence of diarrhea, the variable ownership of feces disposal facilities was the most dominant factor with Exp B 18.267 (p-value 0.003; 95% CI: 2.750-121.334), and the quality of clean water are variables that influence the incidence of diarrhea with Exp B 5.763 (p-value 0.026; 95% CI: 1.234-26.904), food and drink sanitation are variables that influence the incidence of diarrhea with Exp B 12.451 (p-value 0.004; 95% CI: 2.190 - 70.773). Conclusion: It concludes that diarrhea among infants has a dominant relationship of water sanitation, disposal sanitation, and food sanitation as determinants. It needs to improve basic sanitation to decrease the count of diarrhea.